O pedagogo nas redes públicas de Educação Básica e Profissional: perfil-formação-atuação no Instituto Federal (campus Serra) e na Escola Estadual Arnulpho Mattos - Baldan, Waldirlene Telles Coutinho (2023)
This dissertation project analyzed the work of the pedagogue in basic education integrated with professional education. We believe that his profile, training and performance explain the way in which he mediates the daily issues of students and teachers that intersect within the schooling and professionalization process. Methodologically, we intend to observe, through qualitative documentary and field research, the various aspects that define the praxis of this professional located in state and federal public networks. To this end, we carried out a comparative study of the profile, training and performance of this professional in his action as a manager, trainer and/or articulator of the teaching-learning process in two realities where secondary education is integrated with technical education. We consider the pedagogue who works in these realities as an organic intellectual who organizes, mobilizes and monitors school practice in order to promote the integral human formation of students. Initially, we analyzed the institutional records that describe the characteristics of the pedagogue's profiles, ties and working conditions and, subsequently, we listened to the research subjects through semi-structured interviews (recorded on videos) to understand their role in this type of teaching stage at the Federal Institute of Campus Serra and the Arnulpho Mattos State School. The documentary analysis demonstrated 03 positions in the pedagogical mediation function: in the state network the position of pedagogue and pedagogical coordinator, in Ifes the position of pedagogue and TAE. As for the requirements element, in the state network it requires experience in teaching and there are more stages in the competitions. In terms of remuneration, there is a salary disparity among professionals, those in the federal network receive much more compared to those in the state network, a fact that implies the insertion, training and performance of the professional as it reveals their working conditions, in addition we realize that the professionals' responsibilities are many. in these spaces and their responsibilities will vary according to the context in which they will work. The subjects' speech highlighted the absence of the practice of continued training with teachers, lack of training for teachers in the technical area, pedagogical legitimacy regarding the recognition and acceptance of the pedagogue's authority result in difficulties for the pedagogue's performance. In this way, the pedagogue must assume his role as mediator of pedagogical practice, as an organic intellectual, reaffirming and/or redefining his place in professional education. We believe that the current context of transformations in secondary education and technical education offers even more contradictions for pedagogical action committed to integral human formation.